Bleeding green: Sustainability in practice in a clinical skills teaching laboratory - Wesam Alyeddin; Sarah Peters; Adrianna Aleksandra Zembrzycka; Laura Hudson; SanYuMay Tun (Elsevier, 2022)
To reduce the environmental sequelae associated with medical education, at Oxford Medical School we have piloted a scheme since Spring 2020 to clean, repackage and then reuse non-sharp, traditionally 'single-use-only' equipment used in clinical skills training. Here we summarize the progress made by April 2022, which includes substantial reductions in the amount of equipment we have needed to procure, the quantities of clinical waste sent for disposal, and the associated financial costs. We estimate that annually our project results in more than 247 kg of reusable equipment being diverted from clinical waste at our institution. It has been crucial to ensure that equipment is recycled to a standard which still provides students with a safe learning experience which closely simulates the real clinical environment. Meeting the ongoing demand for clinical equipment essential to the day to day running of the clinical skills laboratory has also required consistent work. However, through this project we have developed methods for reusing equipment in the clinical skills setting which overcome these challenges. The Standard Operating Procedures provided here are designed to enable other clinical skills centers to introduce similar initiatives, so that collectively we may work to reduce the environmental impact of clinical skills teaching. This project is part of a wider movement within Oxford Medical School to include sustainability as a cross-curricular theme, and provides students with firsthand experience of how their work setting can be adapted to reduce its environmental impact.